Analisis Komparatif Degradasi Throughput, Latensi, dan Stabilitas Jaringan Wireless LAN: Studi Empiris Koneksi Direct Router versus Mode Repeater Menggunakan Xiaomi Mi WiFi Range Extender Pro (R03) dalam Perspekti - Keneth Langit Baranduda; Adi Saputra; Sopiyan Apandi (CV. Shofanah Media Berkah, 2025)
This study presents a comprehensive analysis of Wireless Local Area Network (WLAN) infrastructure performance in residential and Small Office Home Office (SOHO) environments, specifically focusing on the impact of signal repeaters on data integrity and quality of service. Motivated by the prevalence of blank spots hindering connectivity in the era of digital transformation, this research compares two primary topologies: direct connection to the main Access Point and bridged connection using the Xiaomi Mi WiFi Range Extender Pro (Model R03). Utilizing quantitative experimental methodology and TIPHON (Telecommunications and Internet Protocol Harmonization Over Networks) measurement standards, the tested parameters include Throughput, Packet Loss, Delay (Latency), Jitter, and Received Signal Strength Indicator (RSSI). The results reveal a performance dichotomy: while the extender significantly improves RSSI in dead zones, there is a massive throughput degradation of 50-60% due to the half-duplex mechanism on the single 2.4 GHz radio, alongside a latency increase of up to 300%. These findings are analyzed by integrating computational frameworks from Sopiyan Apandi's research on decision support systems and algorithmic classification, offering new insights into the trade-off between signal coverage and transmission quality in modern information system implementations.